How the Macroeconomic and Financial Structure Affects the Firm Value of a Large Telecommunication Company in Indonesia - Hanung Tyas Saksono; Agus Maolana Hidayat; Sita Deliyana Firmialy (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2024)
TELKOM's strategic initiative, referred to as 5BM, acknowledges the company's considerable assets but notes that it has not yielded substantial profits. To address this, TELKOM has devised this strategy to improve its firm value. This study seeks to contribute to this goal by conducting research focused on analyzing the company's financial structure and evaluating the effects of financial structure, considering macroeconomic factors like interest rates, to enhance its overall value. The research employs a quantitative approach, using TELKOM’s financial data from 2014 to 2024, with variables such as firm size, liquidity ratio, leverage ratio, investment opportunity, efficiency level, profitability, and interest rates. The study applies multiple linear regression to assess the relationships between these independent variables and firm value, using Tobin’s Q as a measure of firm value. Descriptive statistical analysis is also conducted to summarize the characteristics of each research variable. Findings reveal that leverage negatively affects firm value, while firm size, liquidity, investment opportunity, efficiency level, and profitability have positive impacts. Although interest rates and dividend policy also contribute to firm value, their effects are not statistically significant. These results provide insights into the importance of TELKOM's financial structure in enhancing its market valuation.